Cell-specific Nav1.6 knockdown reduced astrocyte-derived Aβ by reverse Na+-Ca2+ transporter-mediated autophagy in alzheimer-like mice - Xin Wang; Wei Wu; Guang Yang; Xue-Wei Yang; Xu Ma; Dan-Dan Zhu; Kabir Ahmad; Khizar Khan; Ying-Zi Wang; Ao-Ran Sui; Song-Yu Guo; Yue Kong; et al. (Journal of Advanced Research)
Introduction: Nav1.6 is closely related to the pathology of Alzheimer’s Disease (AD), and astrocytes have recently been identified as a significant source of β-amyloid (Aβ). However, little is known about the connection between Nav1.6 and astrocyte-derived Aβ. Objective: This study explored the crucial role of Nav1.6 in mediated astrocyte-derived Aβ in AD and knockdown astrocytic Nav1.6 alleviates AD progression by promoting autophagy and lysosome-APP fusion. Methods: A mouse model for astrocytic Nav1.6 knockdown was constructed to study the effects of astrocytic Nav1.6 on amyloidosis. The role of astrocytic Nav1.6 on autophagy and lysosome-APP(amyloid precursor protein) fusion was used by transmission electron microscope, immunostaining, western blot and patch clamp. Glial cell activation was detected using immunostaining. Neuroplasticity and neural network were assessed using patch-clamp, Golgi stain and EEG recording. Behavioral experiments were performed to evaluate cognitive defects. Results: Astrocytic Nav1.6 knockdown reduces amyloidosis, alleviates glial cell activation and morphological complexity, improves neuroplasticity and abnormal neural networks, as well as promotes learning and memory abilities in APP/PS1 mice. Astrocytic Nav1.6 knockdown reduces itself-derived Aβ by promoting lysosome- APP fusion, which is related to attenuating reverse Na+-Ca2+ exchange current thus reducing intracellular Ca2+ to facilitate autophagic through AKT/mTOR/ULK pathway. Conclusion: Our findings unveil the crucial role of astrocyte-specific Nav1.6 in reducing astrocyte-derived Aβ, highlighting its potential as a cell-specific target for modulating AD progression.